Evaluación ética de proyectos de investigación: una experiencia pedagógica, Universidad de Antioquia, Colombia (2006)
ABSTRACT: In all the moments of the development of a research process, since its inception, assessment of the question, objectives discussion, methodology, diffusion, a parallel process is to be accomplished to insure self-regulation and follow- up of the different investigative phases. Conviction- ethics and responsibility-ethics should always be present in the investigator in order to achieve wellbeing for the researches, the subjects of the investigation and for science. The conclusion is that the evaluation of investigation projects, as part of the validating process of new knowledge, should include an evaluation grounded in virtue- ethics, conviction and responsibility orientated towards the advancement of Science and the progress of mankind.